PENGARUH LATIHAN VARIASI SHOOTING TERHADAP KETERAMPILAN KETEPATAN SHOOTING SSB U-12 SUNGAI APIT KABUPATEN SIAK - M.Kamaruddin Angga S; Zainur Zainur; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The problem in this study is "The effect of variations in shooting practice towards shooting accuracy skills SSB U-12 Sungai Apit Siak district" so that athletes can perform and play much better in the future and especially after research and find out if there is an increase in variations in shooting practice in football games to balance the opponent's game and achieve maximum results in the future. The form of this study is (using the only group of pree-test post-test design approach) with the population of football players in the SSB U-12 Sungai Apit Siak district. The sample in this study are all populations of 16 people.The sampling technique in this study uses total sampling technique (all populations). The instrument used in this study used the Shooting at the ball test, which aims to determine the effect of variations in shooting practice towards shooting accuracy skills SSB U-12 Sungai Apit Siak district. The data were then processed with statistics to test the normality using the lilifours test at a significant level of 0.05 α. The proposed hypothesis is that the effect of variations in shooting practice towards shooting accuracy skills SSB U-12 Sungai Apit Siak district. Based on the normal test analysis, data X produces Lcount of 0.213 and Ltable of 0.220, which means Lcount < Table. While Y-variable produces Lcount equal to 1,753 and Ltable equals 15,096. This means Lcount < LTable. There are averages based on the analysis of statistical data variable X 32,87 and the average variable Y is 51,50, then the data is normally distributed. There is, for example, the effect of variations in shooting practice towards shooting accuracy skills SSB U-12 Sungai Apit Siak district.Key Words: Practice Shooting Variations, Shooting Accuracy Skills